Los estilos de aprendizaje en la lectoescritura de los estudiantes de 3er año de educación básica paralelo A de la escuela de educación básica IV Centenario n° 1 de la ciudad de Loja, periodo marzo – noviembre 2013 – lineamientos alternativos - Ramon Yanez, Sthefany Micaela (2014)
The investigation was headed for the purpose of conducting a study of "Learning Styles in Student Literacy 3RD Year of Parallel Basic Education" A "School of Basic Education" IV Centenario No. 1 "of the City of Loja, period March to November 2013, the research is descriptive-explanatory, the analytic-synthetic, inductive, quantitative and qualitative methods were used; instruments such as watching guides learning styles, stages of literacy, neurolinguistic test preferences for children on learning styles and surveys. These methods and tools were used to achieve the results of the problem; with a population of 420 students and 26 teachers took a total sample of 32 people which corresponds to 27 students and five teachers The preparation of the literature review formed by collecting information from books, articles and websites, is organized by learning styles, theories, classes; stages of literacy, conceptualization, processes, and finally learning styles literacy. Found that learning style is more prevalent in students corresponds to the visual style, in which students preferably require learning through pictures, pictographs, graphics, films, while stage Literacy in which most are students corresponds to the Alphabetical stage is to refer to students who have a kinesthetic style are in a syllabic-alphabetic stage not age-appropriate. Given these findings led to recommendations center officials, teachers and parents are raised, so they know the learning styles of individual students and the level of literacy in order to implement strategies in the classroom. The research was of great importance, as it was known learning styles and how they affect was evident in the stage of literacy students. To reduce the problem encountered in the research process, a psychoeducational workshop entitled intends, "Learning Styles a cornerstone in the development of Literacy"